2007
DOI: 10.1016/j.ydbio.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expression of stabilized β-catenin delays maturation of radial glial cells into intermediate progenitors

Abstract: Transgenic mice expressing stabilized beta-catenin in neural progenitors develop enlarged brains resulting from increased progenitor expansion. To more precisely define beta-catenin regulation of progenitor fate, we employed a conditional transgenic approach to delete the beta-catenin regulatory domain from neural progenitors, resulting in expression of stabilized protein from its endogenous promoter in these cells and their progeny. An increased fraction of transgenic cortical cells express the progenitor mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 58 publications
10
99
1
1
Order By: Relevance
“…To functionally validate the close relationship between BP generation and microglia recruitment into the VZ/SVZ, we next assessed whether defective neurogenesis might influence Iba1 þ cell recruitment or positioning into the cerebral cortex. We first analysed Gfap Cre /b-Catenin Ex3 mice owing to their propensity to express a stabilized and constitutive active form of b-catenin in cortical RG leading to a dramatic impairment of Tbr2 þ cell generation 29,30 . At E14.5 the expression of Cxcl12 was almost completely abolished in the cortical SVZ of Gfap Cre /b-Catenin Ex3 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To functionally validate the close relationship between BP generation and microglia recruitment into the VZ/SVZ, we next assessed whether defective neurogenesis might influence Iba1 þ cell recruitment or positioning into the cerebral cortex. We first analysed Gfap Cre /b-Catenin Ex3 mice owing to their propensity to express a stabilized and constitutive active form of b-catenin in cortical RG leading to a dramatic impairment of Tbr2 þ cell generation 29,30 . At E14.5 the expression of Cxcl12 was almost completely abolished in the cortical SVZ of Gfap Cre /b-Catenin Ex3 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mice carrying a constitutive active form of b-Catenin 46 in RG-a genetic alteration that prevents RG to acquire the BP phenotype and to differentiate into Tbr2 þ cells 29,30,47 -the reduction of BP affected Cxcl12 expression in the SVZ and the number of microglia was reduced to B60%. In Pax6 Sey/Sey mice, carrying a null allele for the transcription factor Pax6, Tbr2 þ cells were greatly reduced, Cxcl12 expression was suppressed into the SVZ 6 and a significant reduction of microglia was observed.…”
Section: E145mentioning
confidence: 99%
“…Ectopic expression of nmMlck was achieved by using an untagged plasmid (pCMV6 vector) containing the full-length cDNA for the mouse Mylk gene (Origene Technologies, MD). Ectopic expression of transcriptionally active bcatenin (Wrobel et al, 2007) was achieved by using a plasmid (pCAG-GFP vector) containing a mutated Ctnnb1 gene (encoding a protein with a deletion of the first 90 amino acids of b-catenin, Addgene plasmid 26645; Addgene, MA). The introduction of siRNA duplexes and plasmids was achieved using the Nucleofector kit (Amaxa Biosystems, MD).…”
Section: Gene Knockdown and Transfermentioning
confidence: 99%
“…It is therefore of great interest to elucidate which progenitor populations and which steps in neuron production are being affected by this pathway. Accumulating evidence suggests that activation of the Wnt--catenin pathway promotes proliferation of neural precursor cells (NPCs) that include apical progenitors and basal progenitors (Chenn and Walsh, 2002;Woodhead et al, 2006;Wrobel et al, 2007;Zechner et al, 2003). For instance, persistent expression of a stabilized form of -catenin in NPCs results in an enlarged brain accompanied by excess proliferation of NPCs, presumably due to increased cell cycle re-entry (Chenn and Walsh, 2002;Wrobel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that activation of the Wnt--catenin pathway promotes proliferation of neural precursor cells (NPCs) that include apical progenitors and basal progenitors (Chenn and Walsh, 2002;Woodhead et al, 2006;Wrobel et al, 2007;Zechner et al, 2003). For instance, persistent expression of a stabilized form of -catenin in NPCs results in an enlarged brain accompanied by excess proliferation of NPCs, presumably due to increased cell cycle re-entry (Chenn and Walsh, 2002;Wrobel et al, 2007). In addition to the proliferation-stimulating roles of Wnt signaling, it has been shown that the Wnt--catenin pathway instructs neuronal differentiation of NPCs during neocortical development (Guillemot, 2007;Hirabayashi et al, 2004;Israsena et al, 2004;Lyu et al, 2008;Muroyama et al, 2004;Zhou et al, 2006).…”
Section: Introductionmentioning
confidence: 99%